Assessing the Effects of Plastic Bans on Businesses in Cabanatuan City, Nueva Ecija - Macaso, Mark Edrian P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study investigates the repercussions of the ban on Plastic Bags Business in Cabanatuan City, aiming to define respondent profiles, highlight encountered issues, evaluate business aspects, and propose strategies to address the ban's impact. It seeks to understand the ban's effect on sales/profits and weighs the advantages and disadvantages of plastic bag use. Utilizing a questionnaire, the researcher surveyed ten respondents across two public markets in Cabanatuan City. The focus encompassed problems faced, delving into marketing, financial, and socio-environmental aspects. Findings suggest that despite the ban, plastic bag owners perceive their business as profitable. They attribute this profitability to the perceived greater utility of plastic bags compared to alternative eco-friendly options. The study's significance lies in shedding light on the ban's impact on business operations and financial viability. It emphasizes the perceived profitability of plastic bag sales despite the ban, challenging assumptions about the ban's detrimental effects on business. In essence, the study examines how the ban affects the Plastic Bags Business in Cabanatuan City, underlining the resilience of plastic bag sales despite the prohibition. The insights gained could inform policymakers, businesses, and stakeholders about the complexities and nuances surrounding such bans and their actual impact on businesses and the environment.